In the Shadow of the Big House - the Little People in History - Hoerder, Dirk (Labour / Le Travail, 2000)
Discusses French, German and American approaches to writing social history, and why the author, a German, found a home in the French tradition of Marianne Debouzy, whom he also came to know. Illustrates how small stories can illuminate the bigger historical picture.